2010
DOI: 10.5137/1019-5149.jtn.3320-10.1
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of the arteriovenous malformations of the brain initially presented by hemorrhage – analysis of a clinical series of 39 patients

Abstract: AIm: AVM because of outstanding tendency toward bleeding, even though 20 times more rare then aneurysm on the blood vessels of the brain and her own specific anatomical structure even today represents big neurosurgical challenge. mAterIAl and methOds: Series which is shown here consists of 39 patients which were hospitalized in the institute for neurosurgery of the Clinical Center of Serbia in the period between 1995 and 2004. This group was exposed to symptomatic therapy or it was estimated that surgery, embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Although not from a randomized sample, similar failure was reported by Padilla‐Vazquez et al . and Tasic et al …”
Section: Discussionsupporting
confidence: 82%
“…Although not from a randomized sample, similar failure was reported by Padilla‐Vazquez et al . and Tasic et al …”
Section: Discussionsupporting
confidence: 82%
“…Drain age veins have 6-10 times greater distensibility of the sup ply ing ar tery and may con tain three times the vol ume of blood from the ar tery, and the com pli ance of their 18-30 times higher than in the ar ter ies. Spetzler-Mar tin's gra da tion is a sta tis ti cal con fir ma tion of har mo niz ing po si tions neu ro sur geons and neuroradiologists with re spect to an a tom i cal fea tures of the brain AVM that were pre dic tors of poor out come in pa tients if it were left to the nat u ral course of the disease [6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hem or rhage in pa tients with ep i lepsy as the ini tial symp tom is about 1 to 2.3% per an num. Ev ery fourth pa tient with sei zures as an ini tial symp tom will have hem or rhage [6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Lately, in 2011, Tasic et al reported an incidence of about 7.7% of IVH, 23.1% of SAH and 12.8% of combined bleeding in a series of 39 patients with ruptured AVMs, but they didn't distinguish the influence of the different hemorrhagic patterns on the final outcome [31].…”
Section: Relationship Between Bleeding Pattern and Outcomementioning
confidence: 97%